DIGITAL TRANSFORMATION OF AFGHANISTAN BANKING: EXPLORING E-BANKING TRENDS AND IMPACTS - Hakimi, Musawer; Aslamzai, Sebghatullah; Adhi, Nurseto; Hakimi, Shohib (KEUNIS, 2024)
Afghanistan's Electronic Banking (E-Banking) landscape is experiencing a transformative shift amidst post-conflict challenges, technological innovation, and evolving societal dynamics. This research delves into the complex landscape of E-Banking adoption in the Afghan banking sector, unravelling the intricate relationships among technological innovation, regulatory frameworks, and customer dynamics. With 180 participants in a cross-sectional design, combining quantitative survey data and qualitative insights from interviews, the study employs regression and correlation analysis, ANOVA, and t-tests for preliminary analysis. Exploring the relationships between variables, operational efficiency, and customer perceptions, ethical considerations uphold participant confidentiality. The study's significance lies in contributing to academic discourse and offering practical insights into the Afghan banking industry, shedding light on the nuanced dynamics of E-Banking adoption. The findings provide valuable implications for policymakers and financial institutions by emphasising technology, regulation, and customer-centric perspectives. Navigating post-conflict challenges, this research aims to offer a comprehensive understanding of the ongoing digital transformation.The inclusion of a complete conclusion underscores the study's potential impact on shaping interventions for sustainable growth in Afghanistan's financial sector.